Gene–environment interaction involved in cholangiocarcinoma in the Thai population: polymorphisms of DNA repair genes, smoking and use of alcohol. Issue 10 (21st October 2014) - Songserm, Nopparat; Promthet, Supannee; Pientong, Chamsai; Ekalaksananan, Tipaya; Chopjitt, Peechanika; Wiangnon, Surapon
Abstract : Objective: Cholangiocarcinoma (CCA) is the most common malignancy in a Northeast Thai population. Smoking and alcohol drinking are associated with the production of free radical intermediates, which can cause several types of DNA lesions. Reduced repair of these DNA lesions would constitute an important risk factor for cancer development. We therefore examined whether polymorphisms in DNA base-excision repair (BER) genes, XRCC1 G399A and OGG1 C326G, were associated with CCA risk and whether they modified the effect of smoking and alcohol drinking in the Thai population. Design: A nested case–control study within the cohort study was conducted: 219 participants with primary CCA were each matched with two non-cancer controls from the same cohort on sex, age at recruitment and the presence/absence of Opisthorchis viverrini eggs in stools. Smoking and alcohol consumption were assessed on recruitment. Polymorphisms in BER genes were analysed using a PCR with high-resolution melting analysis. The associations were assessed using conditional logistic regression. Results: Our results suggest that, in the Thai population, polymorphisms in XRCC1 and OGG1 genes, particularly in combination, are associated with increased susceptibility to CCA, and that their role as modifiers of the effect of smoking and alcohol consumption influences the risk of CCA. Conclusions: Better ways of reducing habitual smoking and alcohol consumption, targeted towards subgroups which are genetically susceptible, are recommended. CCA is a multifactorial disease, and a comprehensive approach is needed for its effective prevention. This approach would also have the additional advantage of reducing the onset of other cancers.